Estudo sobre os efeitos do envolvimento na congruência entre organizadores e patrocinadores de eventos esportivos - Santos, Luiz Silva dos (2021)
Sponsorship has been increasingly used in marketing activities. Companies are investing and spending significant amounts of money annually on sponsorships. Among sponsorship expenditures, sports represent a significant and important part of resources. Congruence and involvement are important factors that affect the results of marketing communications associated with sponsorship. This study aimed to investigate the effect caused by the involvement with the brand, the sponsor's product and the sport event, in the congruence between the organizer and the event sponsor, in relation to the sponsor's credibility and its effects on attitudes and intentions of consumers. The sample was composed of 700 people who participated in three street running events held in the City of São Paulo. Data were analyzed using structural equation modeling based on estimation models of partial least squares adjustments. The results indicated that a positive evaluation attributed to the sponsor increases the perceived credibility in relation to the sponsorship. However, the assessment attributed to the organizer did not influence the perception of credibility attributed to the sponsor by the participants of the event. The sponsor's credibility is positively influenced by the consumer's involvement with the sponsoring brand's products and the event. A sponsoring company perceived as credible positively influences consumer attitudes towards the sponsor, the organizer and the event. This favorable relation was also found in the purchase intentions and a positive word of mouth. The credibility of the brand is related to the consumer's intention to buy the sponsor's products and a positive word of mouth about the event. In turn, the sponsor's credibility depends on the following congruence relations: between the event organizer and the sponsor, moderated by the involvement with the sponsor's product and by the involvement with the event; between the product and the event sponsor, moderated by the involvement with the product. This study contributes to a better understanding of how congruence provides to the sponsor's perception of credibility and the importance of including the event organizer in this process. The adjustment of the sponsor with the event organizer is a central factor for a successful sponsorship campaign. Therefore, it is beneficial for companies to select sports sponsorships in which a certain fit between the event and the sponsor is possible. A significant positive main effect of involvement with the sponsor's products was also found. Consequently, companies must support sports, proposing activities that develops the consumer involvement with their products. As companies prioritize sponsorship benefits and purchase intentions as a sales indicator, congruence between a sponsor and an organizer can prove to be a valuable criterion for event sponsorship selection. The results of this study enable the development of strategies to improve the purchase intention and a positive word of mouth of participants of a sport event.